2007
DOI: 10.1159/000111702
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hepatocellular Carcinoma in Japan: Consensus-Based Clinical Practice Manual Proposed by the Japan Society of Hepatology

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death not only in Japan but worldwide. Clinical Practice Guidelines for HCC were published in 2001 by the European Society of Study of the Liver (EASL) and in 2005 by the American Association for the Study of Liver Disease (AASLD). However, these guidelines have proven to be somewhat unsuitable for Japanese patients. In 2005, supported by the Japanese Ministry of Health, Labor and Welfare, Evidence-Based Clinical Practice Guidelines for HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
344
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(355 citation statements)
references
References 51 publications
2
344
0
9
Order By: Relevance
“…4,7,8 In contrast, other studies found that the JIS scoring system was a better model in comparison with the CLIP and BCLC staging systems. 12,13,30 Several factors may contribute to these discrepancies. The characteristics of tumor-related variables, the relative score weighted for each variable, preferred treatment modality in different centers, the number of patients analyzed, the pattern of patient referral and the etiology of cirrhosis could all or in part influence the final results.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 In contrast, other studies found that the JIS scoring system was a better model in comparison with the CLIP and BCLC staging systems. 12,13,30 Several factors may contribute to these discrepancies. The characteristics of tumor-related variables, the relative score weighted for each variable, preferred treatment modality in different centers, the number of patients analyzed, the pattern of patient referral and the etiology of cirrhosis could all or in part influence the final results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, imaging of 1-to 2-cm nodules would miss the diagnosis of HCC in up to 38% of cases. More recently, when hypovascular nodules are detected by MDCT and dynamic MRI, the guidelines published by the Japan Society of Hepatology recommend the use of Sonazoid-enhanced US and SPIOenhanced MRI [224]. When uptake by Kupffer cells is reduced in the Kupffer phase of SPIO-enhanced MRI, malignancy should be highly suspected [214,225,226].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
“…On the basis of the results of these studies, the guidelines published by the EASL [334] and the American Association for Study of Liver Diseases [335] recommend TACE as a first-line, noncurative therapy for nonsurgical patients with large/ multifocal HCC who do not have vascular invasion or extrahepatic spread (level I). In addition, according to the guidelines published by the Japan Society of Hepatology [224], hepatectomy or TACE is recommended if there are two or three tumors of less than 3-cm diameter, and TACE or hepatic arterial infusion chemotherapy is recommended if there are more than four tumors. In addition, TACE can be performed in patients at the early stage in whom RFA cannot be performed because of tumor location (proximity to a gallbladder, biliary tree, or blood vessel) or medical comorbidities [198].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…The new UCA Sonazoid provides Kupffer imaging, which is extremely stable and tolerable for multiple scanning at least up to 60 min in the post-vascular phase, and may further improve the detection rate of HCC with CEUS [41] . The analysis of Kupffer function provides essential information compared with other contrast agents [17,42] . CEUS with Sonazoid detects liver malignancy as defects on the sinusoidal phase with a high sensitivity of 95%, specificity of 93%, positive predictive value of 99%, and negative predictive value of 97% [43] .…”
Section: F E D C B Amentioning
confidence: 99%